2012 IEEE 20th Annual Symposium on High-Performance Interconnects 2012
DOI: 10.1109/hoti.2012.14
|View full text |Cite
|
Sign up to set email alerts
|

Occupancy Sampling for Terabit CEE Switches

Abstract: One consequential feature of Converged Enhanced Ethernet (CEE) is losslessness, achieved through L2 Priority Flow Control (PFC) and Quantized Congestion Notification (QCN).We focus on QCN and its effectiveness in identifying congestive flows in input-buffered CEE switches. QCN assumes an idealized, output-queued switch; however, as future switches scale to higher port counts and link speeds, purely output-queued or sharedmemory architectures lead to excessive memory bandwidth requirements; moreover, PFC typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…In this experiment, we used the QCN-standard flow marking scheme, which sends the CNMs to the most recently received frames. In our design, we have corrected this shortcoming with an occupancy sampling flow-marking scheme for QCN, which sends the CNMs to the flow with the largest occupancy in the monitored payload buffer pool [5]. Figures 10(c,d) demonstrate that our rectified flow-marking scheme, with congestion points at the inputs, performs in par with standard QCN at switch outputs.…”
Section: Congestion Control For Lossless Trafficmentioning
confidence: 85%
See 3 more Smart Citations
“…In this experiment, we used the QCN-standard flow marking scheme, which sends the CNMs to the most recently received frames. In our design, we have corrected this shortcoming with an occupancy sampling flow-marking scheme for QCN, which sends the CNMs to the flow with the largest occupancy in the monitored payload buffer pool [5]. Figures 10(c,d) demonstrate that our rectified flow-marking scheme, with congestion points at the inputs, performs in par with standard QCN at switch outputs.…”
Section: Congestion Control For Lossless Trafficmentioning
confidence: 85%
“…In a previous publication [5], we found that, for unicast traffic, placing the congestion points at the inputs instead of outputs improves QCN's fairness and reduces the bandwidth overhead of CNMs. Furthermore, for multicast traffic, this alternative will generate at most one CNM per multicast frame, whatever the fanout of the flow may be.…”
Section: Congestion Control For Lossless Trafficmentioning
confidence: 97%
See 2 more Smart Citations
“…• Congestion detection at switch input buffers: Neeser et al 14 suggested the use of input-buffer occupancy as a congestion indicator, which provides better fairness and improved detection of offending and victim flows. When generating a CNM, they also selected a victim packet randomly from the complete buffer, not necessarily the packet in the head, in order to improve fairness.…”
Section: Alternatives For Buffer Sampling and Congestion Detectionmentioning
confidence: 99%